Family Hope Program Policy (PKH) In Improving Family Welfare In Bone Bolango County - Safitri, Vincentia Violeta Eka; Abdussamad, Juriko; Isa, Rusli (International Journal of Public Administration Studies, 2024)
The research aims to find out and describe the Implementation of the Family Hope Program (PKH) policy in improving family welfare in Huangobotu Village, Kabila Bone Subdistrict, Bone Bolango Regency, viewed from aspects such as standards and targets, resources, inter-organizational communication, social, economic, and political conditions, characteristics of implementing organizations, and the attitudes of implementers. This research uses a descriptive approach with qualitative data analysis. Data collection techniques include observation, interviews, and documentation. Based on the research findings, it was found that the implementation of the Family Hope Program (PKH) policy in improving family welfare in Huangobotu Village, Kabila Bone Subdistrict, Bone Bolango Regency has been implemented following Minister of Social Affairs Regulation Number 1 Of 2018 regarding the Family Hope Program (PKH), viewed from aspects such as standards and targets, resources, inter-organizational communication, social, economic, and political conditions, characteristics of implementing organizations, and the attitudes of implementers. However, several issues were encountered during is implementation, including insufficient coordination between policy implementers and all relevant parties, lack of updating of beneficiary data resulting in ineffective implementation, and misallocating aid recipients. Thus, it can be concluded that implementing the Family Hope Program (PKH) policy to improve community welfare in Huangobotu Village, Kabila Bone Subdistrict, and Bone Bolango Regency has not been optimally executed. There are still aspects such as standards and targets, inter-organizational communication, and social, economic, and political conditions that need to be improved.